Kesulitan Pembelajaran Mengidentifikasi Makna Puisi Pada Kelas Khusus Olahraga (KKO) di SMA Batik 2 Surakarta - Umi Zulaiah; Andayani Andayani; Atikah Anindyarini (Universitas Palan, 2023)
This study aims to: (1) identifying the lesson planning, (2) analyzing the implementation of learning, and (3) describes learning difficulties in identifying the meaning of poetry in special sport class at Batik 2 Surakarta Senior High School. The method used in this research is descriptive qualitative by case study, and the data resources come from activity, interviewee, and document. Researcher collected the data by using passive observation, document analysis, and indepth interview with interviewee. While deciding purposive sampling for the data collection technique, data analysis was done with flow data analysis. Here are the results of this study. First, teacher’s lesson planning regarding to this material is developed by MGMP’S syllabus in Surakarta followed by the lesson planning development by teacher. Therefore, this study found that teacher’s assesment by designing all instrument for assesment are unnecessary. Furthermore,there is a discrepancy beetwen MGMP’S syllabus and lesson planner made by the teacher in the time allocation. Second, students are found passive and not condusive class academically displayed during learning process, teacher’s lacking in accomodation for teaching method by using lecture method. Third, learning difficulties in identifying the meaning of poetry for student in special sport class are divided by internal factor and external factor. While internal factors are focusing in student lacking literacy and their low enthusiasm for learning, external factors are come from their family and peer friends at class. Their family at home do not require a higher score in Bahasa Indonesia subject because already know their children interests is on sport as an athelete. Keywords: learning difficulties, poetry, special sport class design